Megakaryocytes use in vivo podosome‐like structures working collectively to penetrate the endothelial barrier of bone marrow sinusoids. (25th August 2020) - Eckly, Anita; Scandola, Cyril; Oprescu, Antoine; Michel, Deborah; Rinckel, Jean‐Yves; Proamer, Fabienne; Hoffmann, David; Receveur, Nicolas; Léon, Catherine; Bear, James E.; Ghalloussi, Dorsaf; Harousseau, Gabriel; et al.
Abstract: Background: Blood platelets are anucleate cell fragments that prevent bleeding and minimize blood vessel injury. They are formed from the cytoplasm of megakaryocytes located in the bone marrow. For successful platelet production, megakaryocyte fragments must pass through the sinusoid endothelial barrier by a cell biology process unique to these giant cells as compared with erythrocytes and leukocytes. Currently, the mechanisms by which megakaryocytes interact and progress through the endothelial cells are not understood, resulting in a significant gap in our knowledge of platelet production. Objective: The aim of this study was to investigate how megakaryocytes interact and progress through the endothelial cells of mouse bone marrow sinusoids. Methods: We used a combination of fluorescence, electron, and three‐dimensional microscopy to characterize the cellular events between megakaryocytes and endothelial cells. Results: We identified protrusive, F‐actin‐based podosome‐like structures, called in vivo‐MK podosomes, which initiate the formation of pores through endothelial cells. These structures present a collective and spatial organization through their interconnection via a contractile network of actomyosin, essential to regulate the endothelial openings. This ensures proper passage of megakaryocyte‐derived processes into the blood circulation to promote thrombopoiesis. Conclusion: This study provides novel insight into the in vivo function of podosomes of megakaryocytes with critical importance to platelet production.